Wave riding through time – the contributions of Günther F. Clauss to the field of ocean wave research - Sprenger, Florian; Kosleck, Sascha; Klein, Marco (American Society of Mechanical Engineers, 2022)
Günther F. Clauss is one of the most influential and distinguished international experts in the field of ocean engineering. With 50 years of activities in the field, often in collaboration with national and international colleagues, he has contributed significantly to the visibility and progress of ocean engineering as a research discipline. In his scientific contributions, he has repeatedly established new ideas and set standards. His research contributions include the design, installation and decommissioning of offshore structures, the analysis of loads and motions on floating structures and ships, the development of SAR and oil spill response systems and deep-sea technology. Across all areas, from fundamental to application driven research, one topic always stood out – the investigation, simulation and experimental modelling of natural waves aiming at a comprehensive deterministic analysis of offshore structures and ships in natural sea states and extreme waves. From linear superposition of regular waves to the generation of highly nonlinear wave phenomena, from wave-structure interaction to marine oil spill response technologies this paper attempts the almost impossible task: to deliver an overview over 50 years of research by highlighting selected topics, telling the story of Günther F. Clauss who has conquered the inner space.